Aplikasi Quizlet Dalam Meningkatkan Kosakata Bahasa Jerman - Andi Sari Sartika Fitri; Syamsu Rijal; Burhanuddin Burhanuddin (Universitas Negeri Makassar, 2022)
Abstract. This research is a classroom action research that aims to determine the increase in students' German vocabulary mastery by using the Quizlet application. The research subjects were students of class X IPS 1 SMA Kartika XX-1 Makassar, totaling 19 people and carried out in two cycles. The data in this study consisted of qualitative and quantitative data. Qualitative data was obtained through observation and quantitative data through vocabulary tests (multiple choice, true-false, and matchmaking). The results of data analysis showed that the scores obtained by students on the German vocabulary proficiency test were 70.31% in the first cycle and 96.42% in the second cycle. This shows that the use of Quizlet can improve the vocabulary mastery of X IPS 1 students at SMA Kartika XX-1 Makassar.Keyword: Quizlet, Vocabulary, German